MENGEMBANGKAN MOTORIK ANAK USIA DINI MELALUI PERMAINAN EDUKATIF - Indra Jauharini Amri (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2017)
The game is one medium of education and learning for early childhood that has significance for the growth and development of children including early childhood motor development. While early childhood is an important period for the body and future of the child. And the world of children is the world of play, so learning is needed for advice. Therefore, educational games are very much needed in learning to develop children's motor skills